The BtaF Adhesin Is Necessary for Full Virulence During Respiratory Infection by Brucella suis and Is a Novel Immunogen for Nasal Vaccination Against Brucella Infection - Muñoz González, Florencia; Sycz, Gabriela; Alonso Paiva, Iván M.; Linke, Dirk; Zorreguieta, Angeles; Baldi, Pablo C.; Ferrero, Mariana C. (Frontiers in Immunology, 2019)
Brucella enters their hosts mostly through mucosae from where it spreads systemically. Adhesion to extracellular matrix components or to host cells is important for the infectious process, and is mediated by several adhesins, including the BtaF trimeric autotransporter. Although Th1 responses and gamma interferon (IFN-γ) are important for protection, antibodies able to block adhesions might also contribute to prevent Brucella infection. We evaluated the importance of BtaF for respiratory Brucella infection, and characterized the immune response and protection from mucosal challenge induced by nasal vaccination with recombinant BtaF. While lung CFU numbers did not differ at day 1 p.i. between mice intratracheally inoculated with B. suisM1330 (wild type) and those receiving a ΔbtaF mutant, they were reduced in the later group at 7 and 30 days p.i. For vaccination studies the BtaF passenger domain was engineered and expressed as a soluble trimeric protein. Mice were immunized by the nasal route with BtaF or saline (control group) plus the mucosal adjuvant c-di-AMP. Specific anti-BtaF antibodies (IgG and IgA) were increased in serum, including a mixed IgG2a/IgG1 response. In vitro, these antibodies reduced bacterial adhesion to A549 alveolar epithelial cells. Specific IgA antibodies were also increased in several mucosae. Spleen cells from BtaF immunized mice significantly increased their IL-2, IL-5, IL-17 and IFN-γ secretion upon antigen stimulation. In cervical draining lymph nodes, antigen-experienced CD4+ T cells were maintained mainly as central memory cells. A BtaF-specific delayed-type hypersensitivity response was detected in BtaF immunized mice. Lung cells from the latter produced high levels of IFN-γ upon antigen stimulation. Although nasal immunization with BtaF did not protect mice against B. suis respiratory challenge, it conferred significant protection from intragastric challenge; the splenic load of B. suis was reduced by 3.28 log CFU in immunized mice. This study shows that nasal vaccination with BtaF+c-di-AMP protects against intragastric challenge with B. suis by inducing local and systemic antibody responses, central memory CD4+ T cells and strong Th1 responses. Therefore, although BtaF vaccination did not protect from B. suis respiratory infection, this adhesin constitutes a promising immunogen against mucosal B. suis infection.